Role conflict and role ambiguity among Malaysian Journalists in newsroom decision-making - Faridah Ibrahim (Serdang, Selangor: Universiti Pertanian Malaysia, 2012)
The main objective of the study was to determine the relationship between some selected independent variables with role conflict and role ambiguity perceived by Malaysian journalists in newsroom decision-making.